Quality of service engineering with UML, .NET, and CORBA - Weis, Torben; Ulbrich, Andreas; Geihs, Kurt (International Conference on Software Engineering: Proceedings of the 25th International Conference on Software Engineering : Portland, Oregon; 03-10 May 2003, 2003)
The concern for non-functional properties of software components and distributed applications has increased significantly in recent years. Non-functional properties are often subsumed under the term Quality of Service (QoS). It refers to quality aspects of a software component or service such as real-time response guarantees, availability, and fault-tolerance, the degree of data consistency, the precision of some computation, or the level of security. Consequently, the specification and implementation of QoS mechanisms has become an important concern in the engineering of distributed applications. In this tutorial the attendees will learn how non-functional requirements can be engineered in a systematic way into applications on top of distribution platforms such as CORBA and .NET. The tutorial focuses on two major subjects areas: (1) Specification of QoS properties and (2) implementation of QoS mechanisms in middleware. We present a comprehensive, model-driven approach. It starts with a platform-independent model (PIM) in UML that captures the application QoS requirements. This model is mapped by a tool to a platform-specific model (PSM) tailored for a specific middleware, which is extended with the corresponding QoS mechanisms. Finally, the PSM is translated to code. Participants in this tutorial will get a thorough understanding of general QoS requirements, QoS modeling alternatives and QoS mechanism integration in respect to popular distributed object middleware. Furthermore, we will discuss the pros and cons of CORBA and .NET for QoS engineering. A tool will be demonstrated that eases substantially the modeling stages and the code generation.